Hybrid Imaging-SPECT/CT: making a difference - Sayed, Inayatullah Shah; Moey, Soo Foon (Research Publish, 2016)
Abstract: With the technological advancements in the medical imaging field, the past decade has witnessed a dramatic evolution of multimodality imaging systems. Scientists, technologists and researchers have been able to bring systems in clinical practice, in which two or more standalone diagnostic imaging modalities have been combined. Some of those multimodality imaging systems are: PET/CT, SPECT/CT, PET/MRI and PET/SPECT/CT. With this technique a patient is scanned in a single session and the desired structural and functional information of the organ of interest is achieved. Recent clinical imaging studies in the areas of cardiology,endocrinology, infection, musculoskeletal and neurology has shown, that with multimodality diagnostic imaging, a significant increase in diagnostic accuracy is achieved, as compared to single diagnostic imaging modality. In this review, emphasis is given to the technical aspects and clinical applications of the SPECT/CT hybrid imaging modality.